2014
DOI: 10.1111/cen.12491
|View full text |Cite
|
Sign up to set email alerts
|

Rotation thromboelastometry and the hypercoagulable state in Cushing's syndrome

Abstract: Although FVIII and vWF were abnormal in CS patients, only the initiation clot formation was different in the ROTEM® methodology and no deep vein thrombosis was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 31 publications
0
23
0
2
Order By: Relevance
“…We demonstrated that only the beginning of clot formation (the intrinsic pathway) is altered, and we found increased plasma levels of FVIII, vWF, and D-dimer and decreased activated partial thromboplastin time in patients with active CS. In addition, we observed an increased clot formation speed and higher clot strength in obese CS patients as compared to non-obese CS patients (37).…”
Section: Figurementioning
confidence: 53%
See 3 more Smart Citations
“…We demonstrated that only the beginning of clot formation (the intrinsic pathway) is altered, and we found increased plasma levels of FVIII, vWF, and D-dimer and decreased activated partial thromboplastin time in patients with active CS. In addition, we observed an increased clot formation speed and higher clot strength in obese CS patients as compared to non-obese CS patients (37).…”
Section: Figurementioning
confidence: 53%
“…Most of the studies that have evaluated the procoagulant factors in patients with hypercortisolism have found a decrease in PTT values (5,6,7,14,32,33,34,35,36,37,38) and an increase in the plasma levels of The factor Xa converts prothrombin (factor II) into thrombin (factor IIa) in the presence of ionized calcium and factor Va.…”
Section: Hypercoagulabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, a reduction in activated partial thromboplastin time (aPTT), a marker of the intrinsic system, in CS has been repeatedly described (16,19,24,25,26,33,34,35). Recently, Gadelha et al…”
Section: Coagulation Cascadementioning
confidence: 99%